21.1k views
2 votes
Can someone please help me get the answer in simple terms?

Can someone please help me get the answer in simple terms?-example-1

1 Answer

6 votes

Solution:

Given the expression:


\log _(10)xy^2

From the multiplication law of logarithm,


\log _cAB=\log _cA+\log _cB

thus, we have


\log _(10)xy^2=\log _(10)x+\log _(10)y^2

From the power law of logarithm,


\begin{gathered} \log _cA^b=b*\log _cA \\ =b\log _cA \end{gathered}

this then implies that


\begin{gathered} \log _(10)xy^2=\log _(10)x+\log _(10)y^2 \\ =\log _(10)x+(2*\log _(10)y) \\ =\log _(10)x+2\log _(10)y \\ \end{gathered}

Hence, when the above expression is expanded, we have


\log _(10)x+2\log _(10)y

User GertV
by
4.5k points